2007
DOI: 10.1128/mcb.02234-06
|View full text |Cite
|
Sign up to set email alerts
|

CpG Hypomethylation in a Large Domain Encompassing the Embryonic β-Like Globin Genes in Primitive Erythrocytes

Abstract: There is little evidence addressing the role of CpG methylation in transcriptional control of genes that do not contain CpG islands. This is reflected in the ongoing debate about whether CpG methylation merely suppresses retroelements or if it also plays a role in developmental and tissue-specific gene regulation. The genes of the ␤-globin locus are an important model of mammalian developmental gene regulation and do not contain CpG islands. We have analyzed the methylation status of regions in the murine ␤-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…Recently, we have demonstrated that large domains of DNA hypomethylation are present in the mouse β-globin locus [32], and that developmental changes in γ- and β-globin gene methylation extend beyond the promoter cores [12]. These factors led us to consider whether DNA methylation may influence β-globin locus gene expression through a combinatorial mechanism involving domains of DNA hypomethylation and domains of histone modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that large domains of DNA hypomethylation are present in the mouse β-globin locus [32], and that developmental changes in γ- and β-globin gene methylation extend beyond the promoter cores [12]. These factors led us to consider whether DNA methylation may influence β-globin locus gene expression through a combinatorial mechanism involving domains of DNA hypomethylation and domains of histone modifications.…”
Section: Introductionmentioning
confidence: 99%
“…LCR-mediated silencing is accompanied by changes in replication timing, DNA methylation, and histone modifications (28,(49)(50)(51). The LCR is required for DNA methylation at ectopic sites (11).…”
mentioning
confidence: 99%
“…MLL2 contains a CxxC domain, which mediates binding to non-methylated CpG-rich DNA, 89,90 however the region between the LCR and β maj promoter is quite heavily DNA methylated in adult cells. 46 While it has been proposed that MLL2 could bind to methylated H3K4 through its PHD domains, 91 H3K4me2, 27 and H3K4me3, 21 marks are not continuous across the β-globin locus in adult cells. Therefore, it is unlikely that MLL2 uses these domains for self-propagation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a similar PRMT5/ DNMT3A-mediated process is involved in the formation of DNA hypermethylated domains at the embryonic genes in definitive murine erythroid cells. 46 In addition to histone methylation, nucleosome remodeling and histone deacetylation are likely important for maintaining the mouse embryonic gene in a repressed state, in a similar fashion to the repression of human fetal γ-globin gene, where the transcription factors BCL11A, 47 GATA-1, FOG-1, 47,48 and Ikaros 49 are involved in silencing γ-globin through a mechanism linked to NuRD complex component (Mi-2 and HDAC1) recruitment to the γ-globin gene promoters. 48,49 Notably, in mouse erythroid cells BCL11A forms a complex with all NuRD components, suggesting that this mechanism might be conserved between mouse and human adult erythroid cells.…”
mentioning
confidence: 99%